Water blister geomorphology and subglacial drainage sediments: an example from the bed of the Fennoscandian Ice Sheet in SW Finland - Joni Mäkinen; Christine F. Dow; Elina Ahokangas; Antti Ojala; Kari Kajuutti; Juulia Kautto; Jukka-Pekka Palmu (Journal of Glaciology, 2023)
This study presents the first light detection and ranging (LiDAR)-based morphometric description of a water blister from a past ice-sheet bed caused by rapid supraglacial drainage. The blister formed during the rapid early Holocene deglaciation of the Fennoscandian Ice Sheet (FIS). It is located in southwest Finland within a subglacial meltwater route interpreted to represent the transition from a distributed to a channelized drainage system. A LiDAR digital elevation model was supplemented with sedimentological and ground-penetrating radar data on blister outflow channels and sedimentology of downflow polymorphous mounds and ridges (PMRs). Unlike the water blisters recorded from the rapid drainage of supraglacial lakes on the Greenland Ice Sheet, the smaller blister size here was either due to crevasse or moulin drainage, or was a supraglacial lake drainage that tapped into a pre-existing, relatively efficient drainage system and related semi-sorted sediments, promoting rapid drainage and reworking of PMRs along the meltwater route. The preservation potential or exposure probability of blister marks is presumably low but they can provide important information about evolution of subglacial drainage systems that is of value to modern interpretations of glacial hydrology.